A person-centered exploration of children of immigrants' social experiences and their school-based well-being. Issue 2 (3rd April 2018) - Pieloch, Kerrie A.; Marks, Amy K.; García Coll, Cynthia
ABSTRACT: This study aimed to explore commonalities among discrimination, stereotyping, and peer-related social experiences of children of immigrants, and to see if these experiences might relate to children's school-based well-being. Two age-based cohorts of 294 children and their immigrant parents from Portugal, the Dominican Republic, and Cambodia were interviewed. Person-centered analyses resulted in four unique clusters of children's social experiences. Notably, children in clusters with positive views of cultural in-group and out-group members also reported positive school-based well-being. Person-centered analyses on parent variables found three clusters based on parents' ethnic/racial socialization practices. There was no overlap between parent and child clusters, indicating unique profiles between parent socialization and child social experiences within immigrant families. Implications of connections among social experiences and school-based emotional well-being for children of immigrants are discussed.